Comparison of arthroscopic lavage, needle lavage, and lavage volume on the recovery of colored microspheres from the tarsocrural joint of the horse - Loftin, Patrick Glenn (Kansas State University, 2015)
Objectives: To quantify recovery of colored microspheres from cadaver tarsocrural joints via arthroscopic or needle lavage, and to compare recovery for 1-5L of lavage fluid. Study design: Randomized experimental trial. Methods: 8 adult Quarter Horse cadavers had 1.5 million 15μm, colored microspheres injected into each tarsocrural joint. Each joint was randomly assigned to receive lavage with an arthroscope and egress cannula (group A) or three (1 ingress, 2 egress) 14 gauge needles (group N) with 5L 0.9% NaCl. The egress fluid from each liter of lavage was collected separately, and the number of microspheres present in each recovered liter was determined via spectrophotometry. Results: A significant interaction (p<0.01) was present between treatment group and liter. The number of microspheres recovered in the first liter of lavage fluid was significantly higher in the needle group than in the arthroscope group (p<0.01). For both groups the number of microspheres recovered in the first liter of lavage fluid represented a majority of the total microspheres collected, and was significantly different from the subsequent liters collected (p<0.01). The number of microspheres recovered did not differ between liters 2, 3, 4, and 5, within or between treatment groups. Conclusions: In this model, tarsocrural lavage with three 14-gauge needles was more effective at removing colored microspheres from the joint than arthroscopic lavage, suggesting the number or placement of portals present may be more important than portal size and flow rate. No difference in microsphere recovery was seen with lavage volumes greater than 1L.
Keywords: Horse; Joint lavage; Needle; Arthroscopy; Veterinary Medicine (0778)